2018
DOI: 10.1016/j.artmed.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical motion analysis using discriminative interpretable patterns

Abstract: The proposed approach is an interesting addition to existing learning tools for surgery as it provides a way to obtain a feedback on which parts of an exercise have been used to classify the attempt as correct or incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 54 publications
1
64
0
Order By: Relevance
“…Hand motion studies have also been done in a simulation environment [9,10]. Similar differences in trajectory analysis were also reported by others [16,19,23,36]. Trajectory analysis in these studies showed results similar to those in the present study for the JIGSAWS data ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hand motion studies have also been done in a simulation environment [9,10]. Similar differences in trajectory analysis were also reported by others [16,19,23,36]. Trajectory analysis in these studies showed results similar to those in the present study for the JIGSAWS data ( Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The JHU-ISI Gesture and Skill Assessment Working Set (JIGSAWS) dataset was generated at Johns Hopkins University and is a standardized dataset from simulated RMIS with three exercises (suturing, knot-tying and needle passing) performed by eight participants with varied prior experience [22]. JIGSAWS is the largest publicly available dataset for gesture analysis, and previous work has focused on skill evaluation, gesture classification, gesture segmentation and surgical task recognition [23]. The dataset is fixed and cannot be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have used Raven in experiments studying measurement or acquisition or updating of surgical skills in robotic surgeons [37][38][39]. For example, [37] quantized robotic gestures into strings which were shown statistically able to discriminate skill level.…”
Section: Research Using Ravenmentioning
confidence: 99%
“…Several groups have used Raven in experiments studying measurement or acquisition or updating of surgical skills in robotic surgeons [37][38][39]. For example, [37] quantized robotic gestures into strings which were shown statistically able to discriminate skill level. Another skill assessment study [38] compared performance and learning of trainees between a hands-on user interface device and a contactless control interface based on a low cost (compared to haptic devices) depth sensing camera and hand gestures.…”
Section: Research Using Ravenmentioning
confidence: 99%
See 1 more Smart Citation